The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijerph17197324
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Screen Use and Health Indicators among Infants, Toddlers, and Preschoolers: A Meta-Analysis and Systematic Review

Abstract: Evidence suggests that excessive screen time in early childhood is related to children’s physical and mental health. This study aimed to review the relationships between screen media use and several health indicators in infants, toddlers, and preschoolers. A systematic search was conducted by two independent reviewers on PubMed, Web of Science, Embase, and Cochrane Library to identify the eligible studies, with an end date of 13 August 2019. Included studies (published in English) were peer-reviewed and met th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 114 publications
3
72
1
16
Order By: Relevance
“…In a study from Taiwan, Lin et.al demonstrated a significantly higher cognitive delay among children with increased television exposure (OR 3.9, 95% CI 1.4-5.9) [7]. In contrast to our study, a recent systematic review and meta-analysis revealed that children with excess screen time were at a higher risk of delayed language development, learning problems (language and mathematics), and reading problems [32].…”
Section: Discussioncontrasting
confidence: 99%
“…In a study from Taiwan, Lin et.al demonstrated a significantly higher cognitive delay among children with increased television exposure (OR 3.9, 95% CI 1.4-5.9) [7]. In contrast to our study, a recent systematic review and meta-analysis revealed that children with excess screen time were at a higher risk of delayed language development, learning problems (language and mathematics), and reading problems [32].…”
Section: Discussioncontrasting
confidence: 99%
“…Si bien aún no se ha logrado clarificar de qué manera el uso indiscriminado de pantallas podría afectar tales procesos madurativos, se ha demostrado que la exposición temprana a la televisión se asocia con problemas de atención en los años siguientes (Christakis et al, 2004). Algunos investigadores (Li et al, 2020) han logrado asociar el uso excesivo de pantallas en niñas y niños con indicadores de salud física, conductual y psicosocial, mientras que otros han sistematizado los hallazgos de diversos estudios para discriminar cuáles son las variables que se correlacionan más específicamente con los hábitos de uso de los medios digitales durante la infancia (Duch et al, 2013). Ciertos estudios (Radesky y Christakis, 2016) incluso advierten sobre la necesidad de acompañamiento por parte de los adultos antes de los 2 años, a fin de seleccionar contenidos y establecer límites de exposición.…”
Section: El Uso De Pantallas En La Actualidadunclassified
“…Asimismo, el efecto lumínico de las pantallas produce trastornos del sueño (Krynski et al, 2017;Hill, 2016;AAP, 2016), en particular después de las ocho de la noche, ya que inhibe la secreción de melatonina (Garrison et al, 2011) y dificulta la conciliación del sueño, lo cual puede producir trastornos emocionales y de concentración a largo plazo (Mendieta Pineda, 2017). En efecto, un metaanálisis llevado a cabo recientemente (Li et al, 2020) indicó que el tiempo excesivo frente a una pantalla se asocia con una menor duración del sueño en la primera infancia. Este hallazgo ratifica los resultados de un estudio realizado en el Reino Unido a más de 700 bebés de 6 a 36 meses (Cheung et al, 2017), que revelaron una asociación significativa entre la frecuencia de uso de la pantalla táctil y la cantidad de sueño, así como un inicio del sueño más prolongado.…”
Section: Efectos Posteriores Durante El Desarrollounclassified
See 2 more Smart Citations